Preservice Programs for Rural Environments: Survey and Recommendations - Barbara Jean Jones (Journal of Research in Rural Education, 1986)
Given the number of rural constituencies in the nation and the unique problems facing rural educators, the preparation of teachers for service in rural areas is vital. This study examined the availability of undergraduate preservice or certification programs which prepare students for rural teaching, examined preservice programs for the availability of specific components which meet rural teacher needs, and suggested ways to improve and expand preservice programs for rural educators. A questionnaire was distributed to 456 public and private post-secondary institutions which offered preservice teacher preparation programs in the 27 states defined as rural. The 208 respondents whose data were analyzed indicated that 21 (10.1%) of the institutions offer specializedprograms for teachers planning to work in rural areas, and that about half of the suggestedpreservice components for rural environments are implemented at over half of the institutions (range 58.1% to 90.3070). It was recommended that program planners develop an awareness of the disparities that exist between what is available and what researchers indicate should be available in preservice education for rural environments.